Prevalence of Musculoskeletal Disorders in Patients With Type 2 Diabetes Mellitus - Arif, Mamoona; Ahmed, Jameel; Ahmedani, Yaqoob; Mubashir, Uzma; Ghaffar, Nargis; Memon, Qudsia (Biological and Clinical Sciences Research Journal, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder associated not only with vascular and neurological complications but also with musculoskeletal disorders (MSDs), which can significantly affect mobility, independence, and quality of life. Objective: To determine the prevalence of musculoskeletal disorders among patients with type 2 diabetes mellitus and to identify their association with demographic and clinical factors. Methodology: This descriptive cross-sectional study was conducted at the Department of Medicine, Baqai Institute of Diabetology & Endocrinology (BIDE), Karachi, from January 2024 till June 2024. A total of 143 patients aged 30–70 years with T2DM for at least one year were enrolled using non-probability consecutive sampling. Data were collected through a structured pro forma, which included demographic details, anthropometric measurements, and clinical evaluations using GALS and REMS examinations. Results: Out of 143 participants, 51 (35.7%) were found to have one or more musculoskeletal disorders. The most frequent conditions were adhesive capsulitis (27.5%), carpal tunnel syndrome (17.6%), and diabetic cheiroarthropathy (15.7%). A significant association was observed between MSDs and residence status (p = 0.01), socioeconomic status (p = 0.01), and absence of family history of diabetes (p = 0.01). No significant associations were found with age, gender, duration of diabetes, or education level. Conclusion: Musculoskeletal disorders are highly prevalent among patients with type 2 diabetes mellitus, with periarticular conditions being the most common. Rural residence, low socioeconomic status, and lack of family history were significant risk factors. Routine musculoskeletal screening should be incorporated into diabetic care to ensure early diagnosis, reduce disability, and improve patients’ quality of life.